Neural alignment predicts learning outcomes in students taking an introduction to computer science course - Meir Meshulam (Nature Portfolio, 2021)
Learning and remembering new information is a major challenge for students of all levels. Here, the authors show that “neural alignment” across brains is associated with learning success of STEM concepts in a real-life college course and predicts learning outcomes.